Influence Of Fly Ash Resulted from the Burning of Plants the Properties Of Swelling - Fayyad, Tawfeek (Latakia University Journal -Engineering Sciences Series, 2020)
Fly ash results from the burning of plant materials such as trees after being trimmed or removed, which resulted in the accumulation of large amounts of this material, which is difficult after a certain extent to be removed or buried, resulting in accumulation of environmental problems that harm the living organisms. Hence the idea of taking advantage of these wastes and their use in the field of soil improvement. Experimental results on samples of the soils showed a significant improvement in the physical and mechanical properties of some soils. As a significant increase in the angle of internal friction, a decrease in the swelling pressure as well as a clear reduction in the values of the limits of Atterberg. ينتج الهباب عن حرق المواد النباتية كالأشجار بعد تقليمها أو إزالتها وت تراكم أحياناً كميات كبيرة من هذه المادة يصعب بعد حد معين إزالتها أو طمرها، مما يؤدي إلى مشاكل بيئية تعود بالضرر على الكائنات الحية. من هنا كانت فكرة الاستفادة من هذه المخلفات و استخدامها في مجال تحسين الترب. أظهرت النتائج التجريبية التي أجريت على عينات من الترب الغضارية إلى تحسن واضح للخصائص الفيزيائية و الميكانيكية لبعض هذه الترب. كازدياد واضح في زاوية الاحتكاك الداخلي، نقصان في ضغط الانتفاخ كذلك انخفاض واضح في قيم حدود أتربرغ. مما ينعكس إيجاباً على سلوك التربة الغضارية الانتفاخية.